Evaluation Of The United Nations Security Council Veto In Cases Of Atrocity Crimes - Saffana Khalisha; Sasmini; Ayub Torry Satriyo Kusumo (Fakultas Hukum Universitas Islam Indonesia, 2026)
This research aims to evaluate the use of veto power by the United Nations Security Council (UNSC) concerning human rights violations, particularly atrocity crimes. Permanent member states, such as the United States and Russia, often misuse the veto to protect national interests, undermining the UN’s goals of maintaining international peace and security. Employing a normative legal research method focused on legislation and case studies, the findings reveal that veto usage in atrocity cases obstructs the Security Council’s actions and creates injustices in international law enforcement. The conflicts in Israel-Palestine and Ukraine exemplify how the veto shields human rights violations. The study recommends reforms to the veto mechanism, including establishing an independent assessment body and enhancing transparency in decision-making. Ultimately, it aims to enable the UNSC to more effectively protect human rights and prevent atrocity crimes, contributing to the development of international law and serving as a reference for future research.